Supply and Demand: Special Collections and Digitisation - Erway, Ricky (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
Based on the outcome of an RLG event entitled ‘Digitisation Matters’, the author presents a number of thought-provoking and sometimes provocative ideas to make more of libraries’ special collections available on the web, stressing access and quantity as key factors.